Idea pentarchii jako rękojmia jedności Kościoła w dobie ikonoklazmu. Stanowisko Teodora Studyty - Kashchuk, Oleksandr (Vox Patrum, 2012)
From the first half of the eighth century until the mid-ninth century the Church of Constantinople struggled with heretical iconoclast movement. During the period of iconoclasm, St. Theodore of Studium (759-826) stood at the side of the defenders of the cult of images. He was a great thinker and abbot of the Studium monastery near Constantinople. One of the main themes he discussed was an independant status of Church from secular power, which frequently intervened in issues relating to faith and morals. St. Theodore of Studium wanted to prove that the Church dogmas and rules derive not from emperors, but bishops. In this context, his idea resembles the concept of pentarchy. According to St. Theodore, the guarantee of orthodoxy, which is the basis for the unity of the universal Church, is rooted in ecclesial body of pentarchy. Decisions about divine and celestial dogmas are entrusted to five patriarchs, who should be characterized by unanimity to reach a joint decision at the universal council. All of them together have the highest position in the Church and their consent is necessary for recognition of the ecumenical council. Among the five patriarchs the privileged position has the patriarch of Rome, without whom no ecumenical council can be called. The Roman Church is the reference point and stands at the center of the unity of Church. St. Theodore of Studium considered the primacy of the bishop of Rome not in isolation from other patriarchates but in orbit of the entire Church.